2021
DOI: 10.3389/fcell.2021.685625
|View full text |Cite
|
Sign up to set email alerts
|

Binding Features and Functions of ATG3

Abstract: Autophagy is an evolutionarily conserved catabolic process that is essential for maintaining cellular, tissue, and organismal homeostasis. Autophagy-related (ATG) genes are indispensable for autophagosome formation. ATG3 is one of the key genes involved in autophagy, and its homologs are common in eukaryotes. During autophagy, ATG3 acts as an E2 ubiquitin-like conjugating enzyme in the ATG8 conjugation system, contributing to phagophore elongation. ATG3 has also been found to participate in many physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 108 publications
0
27
0
Order By: Relevance
“…The cohort of autophagy-related (ATG) proteins regulating conventional autophagy, ATG3, ATG5, ATG7 and ATG10 (essential core proteins required for LC3A lipidation) [ 41 , 42 ] were more significantly expressed in the EUG treatments compared to the SPD treatment alone ( Figure 5 A,B). ATG13 involved in both the initiation stage (induction of the ULK1 complex) as well as the autophagosome–lysosome fusion stage [ 43 ], was equally expressed in all three treatments ( Figure 5 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cohort of autophagy-related (ATG) proteins regulating conventional autophagy, ATG3, ATG5, ATG7 and ATG10 (essential core proteins required for LC3A lipidation) [ 41 , 42 ] were more significantly expressed in the EUG treatments compared to the SPD treatment alone ( Figure 5 A,B). ATG13 involved in both the initiation stage (induction of the ULK1 complex) as well as the autophagosome–lysosome fusion stage [ 43 ], was equally expressed in all three treatments ( Figure 5 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Comparable effects were noted between EUG and SPD alone for ATG3, ATG4A, ATG4B, ATG13 and Beclin-1. Given numerous recent reports on SPD stimulation of autophagy [ 11 , 21 , 22 , 23 ], the effect of EUG can likewise be considered significant, based on the increased expression of several crucial core proteins at all stages of autophagic flux: initiation (ATG13) [ 43 ]; nucleation (Beclin-1) [ 11 ]; autophagasome elongation (ATG3, ATG5 and ATG7) [ 41 , 42 ] and autophagosome-lysosome fusion (Beclin-1; ATG13) [ 11 , 53 ]. Interestingly, increased ATG3, responsible for linking LC3-I to PE, with the help of the ATG12–ATG5 conjugate [ 42 ], has also been shown to been inversely associated with apoptopic-inducing caspase-8 expression, placing ATG3 as a novel link between apoptosis and autophagy [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We next studied another autophagy related gene, ATG3, which is important for autophagosome formation [ 21 ]. We calculated the correlation coefficient between HIF-1α and ATG3 expression using Pearson correlation analysis based on TCGA data, which indicated that HIF-1α expression correlated significantly and positively with ATG3 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Atg8-PE recognizes the Atg8-family interacting motif in cargos and promotes autophagosome biogenesis to result in autophagy-mediated degradation [ 26 ]. In the process of autophagy, ATG3 acts as an E2 ubiquitin-like conjugating enzyme in the ATG8 binding system, helping to extend the phagocytic cells [ 27 ]. The combination of ATG12 and ATG3 regulates mitochondrial homeostasis and cell death [ 28 ].…”
Section: Resultsmentioning
confidence: 99%